Music-listening in everyday life: Devices and choice - Krause, Amanda; North, Adrian; Hewitt, Lauren (Sage Publications Ltd., 2015)
Utilizing the Experience Sampling Method, this research investigated how individuals encounter music in everyday life. Responding to two text messages sent at random times between 8:00 and 23:00 daily for one week, 177 participants completed self-reports online regarding their experience with any music heard within a two-hour period prior to receipt of the message. Overall, the radio, mobile MP3 players, and computers featured prominently. Detailed analyses revealed significant patterns in device usage based on time of day; ratings of the music in terms of choice, liking, arousal, and attention; mood; and the perceived consequences of the music. While feeling lethargic associated with recorded music broadcasted in public, in contrast personal music collections promoted contentment. Similarly, devices allowing for personal input were met with positive consequences, like motivation. The current findings imply that the greater control that technology affords leads to complex patterns of everyday music usage, and that listeners are active consumers rather than passive listeners.